The Implementation of Training Programs to Make Tumpeng for the Community - Hamdani Hamdani; A Ismail Lukman; Albert Richart Singal; Mustangin Mustangin; Hepy Tri Winarti; Muhammad Alisalman (Departement of Nonformal Education, Graduate Scholl of Universitas Negeri Yogyakarta, 2022)
The background of this research is the Empowerment of Citizens Learning through a Training Program to make Tumpeng in Sanggar Kegiatan Belajar (SKB) Samarinda give an influence on Knowledge, Attitudes and Skills. The purpose of this study is how the process of implementing the training program makes Tumpeng rice, as well as reviewing factors that inhibit and support the factors and impacts of the Training Program to make Tumpeng in SKB Samarinda City. The type of research used is the Type of Qualitative Research Method. The data sources in this study are the Head of Sanggar Kegiatan Belajar (SKB) Samarinda, Tutors and Learners. Data Collection techniques using Observation, Interviews and Documentation. Data Analysis techniques include Data Collection, Data Reduction, Data Display and Conclusion Drawing. The results of this research are (1) program planning is carried out through the identification of needs to the community (2) the implementation of the program is related to the learning process using methods of delivering material and practice to improve knowledge and skills and (3) evaluation is implemented to see the success of the program. Supporting Factors for Training Programs make Tumpeng is an excellent Learners Response, The Presence of Competent and Experienced Speakers. Factor The existence of other jobs such as gardening.